UMP partners with KOCEL to leverage global online learning platform - Gan, Leong Ming (2019)
Universiti Malaysia Pahang (UMP) recently cemented a five-year partnership with China’s Kocel Group Ltd (KOCEL) with the signing of a Memorandum of Understanding (MoU) at the latter’s National Intelligent Foundry Industry Innovation Centre (NIFI) in Ningxia, China, on April 24, 2019.